2010
DOI: 10.1007/s11071-010-9868-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-tuning fuzzy logic control of crane structures against earthquake induced vibration

Abstract: Self-tuning fuzzy logic controllers (STFLC) for the active control of Marmara Kocaeli Earthquake excited crane structures are studied in this paper. Vibration control using intelligent controllers, such as fuzzy logic has attracted the attention of structural control engineers during the last few years, because fuzzy logic can handle, uncertainties and heuristic knowledge and even non-linearities effectively and easily. The improved seismic control performance can be achieved by converting a simply designed st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…and this Hamiltonian must be negative definite for all and . The following equation can be obtained by substituting (4) into (5):…”
Section: Controller Designmentioning
confidence: 99%
See 2 more Smart Citations
“…and this Hamiltonian must be negative definite for all and . The following equation can be obtained by substituting (4) into (5):…”
Section: Controller Designmentioning
confidence: 99%
“…In literature, there are studies about active seismic control for crane structures. For example, Sagirli et al [5] performed active vibration control studies to decrease the structural vibrations on gantry cranes. A five-degree-of-freedom nonlinear mathematical model which was developed for the gantry cranes and proved by shake table tests in the previous study (Sagirli and Azeloglu [6]) is used and a self-tuning fuzzy logic controller (STFLC) was designed as a control algorithm in the studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few works have been done in the field of seismic control of container cranes. Sagirli et al [8] studied self-tuning fuzzy logic controllers to suppress structural vibrations of a crane under the earthquake excitation and numerical studies proved that the control strategy is a feasible method. Azeloglu et al [9,10] developed the fuzzy PID type controller and a linear matrix inequality based mixed 2 / ∞ state-feedback controller to reduce seismic response of a crane.…”
Section: Introductionmentioning
confidence: 99%
“…It is revealed that the developed mathematical model can be used as a gantry crane model in active vibration control studies in order to decrease the structural vibrations on the gantry cranes. By using the defined mathematical model, to decrease the structural vibrations on gantry cranes, Sagirli et al [9] performed active vibration control studies. The results of the simulation studies show that active vibration control can be successfully performed on gantry cranes.…”
Section: Introductionmentioning
confidence: 99%